The roles of different forms of IL-15 in human melanoma progression - Di Matteo, Sabina; Munari, Enrico; Fiore, Piera Filomena; Santopolo, Silvia; Sampaoli, Camilla; Pelosi, Andrea; Chouaib, Salem; Tumino, Nicola; Vacca, Paola; Mariotti, Francesca Romana; Ebert, Stefan; Machwirth, Markus; et al. (Frontiers in Immunology, 2023)
Background: Melanoma is a lethal skin cancer whose risk is upregulated by the exposure to ultraviolet (UV) radiation. Production of cytokines such as IL-15, induced by the exposure of skin cells to UV rays, could favor melanoma development. The aim of this study is to investigate the possible role of IL-15/IL-15Rα complex in melanoma development. Methods: The expression of IL-15/IL-15Rα complexes by melanoma cells was evaluated both ex vivo and in vitro by tissue microarray, PCR and flow cytometry. The presence of the soluble complex (sIL-15/IL-15Rα) in the plasma of metastatic melanoma patients was evaluated by ELISA assay. Subsequently, we investigated the impact of NK cell activation after rIL-2 starvation followed by exposure to the sIL-15/IL-15Rα complex. Finally, by analyzing public datasets, we studied the correlation between IL-15 and IL-15Rα expressions and melanoma stage, NK and T cell markers and overall survival (OS). Results: Analysis of a melanoma tissue microarray shows a significant progression in the number of IL-15+ tumor cells from benign nevi up to metastatic melanoma. Metastatic melanoma cell lines display a phorbol-12-myristate-13-acetate (PMA)-cleavable membrane bound IL-15, while cultures from primary melanomas express a PMA resistant isoform. Further analysis revealed that 26 % of metastatic patients present long-lasting high plasmatic levels of sIL-15/IL-15Rα. When the recombinant soluble human IL-15/IL-15Rα complex is added to shortly starved rIL-2-expanded NK cells, these cells exhibit strongly reduced proliferation and cytotoxic activity against K562 and NALM-18 target cells. The analysis of public gene expression datasets revealed that high IL-15 and IL-15Rα intra-tumoral production correlates with high expression of CD5+ and NKp46+ (T and NK markers) and significantly correlates with a better OS in stages II and III but not in stage IV. Conclusions: Membrane-bound and secreted IL-15/IL-15Rα complexes are continuously present during progression in melanoma. Of note, according to the tumor stage, while IL-15/ IL-15Rα could initially favor cytotoxic T and NK cells, at stage IV would rather favor the development of anergic and dysfunctional cytotoxic NK cells. In a subgroup of melanoma metastatic patients, the continuous secretion of high amounts of the soluble complex could represent a novel mechanism of immune escape.